The intemperate rainforest : nature, culture, and power on Canada's west coast - Braun, Bruce, 1964- (University of Minnesota Press, 2002)
Bruce Braun examines social, discursive, and political practices through which Canadas West Coast forests have been given meaning and made the site of intense political and ideological struggle. Departing from other work on environmental politics that assumes the "forest" is a constant, The Intemperate Rainforest traces the way West Coast landscapes have been viewed and controlled by explorers, foresters, environmentalists, artists, scientists, adventure travelers, and Native peoples.